Fostering stakeholder engagement in sustainable cultural tourism development in nature-based sites: A case study on using methodological layering of art-based methods - Hong, Li; Lüthje, Monika; Björn, Ella; Miettinen, Satu (Taylor & Francis, 2023)
In this chapter, we explore how the methodological layering of art-based methods (ABMs) can engage various stakeholders in sustainable cultural tourism development in Utsjoki—the northernmost municipality in Finland. The case study area is a dominantly rural and nature-based destination where the Indigenous Sámi community plays an essential role in setting up development priorities. In the Sámi way of life, nature and culture are deeply intertwined, as nature-based livelihoods and using local land and water are important parts of the local culture. The municipality needs new solutions for year-round sustainable tourism to replace the highly seasonal wild salmon fishing tourism on which it previously relied. Tourism activities should be designed collaboratively and not disturb the local way of life. Compared to traditional research methods, the participatory and versatile aspects of ABMs can offer more collaborative approaches to create shared understanding and build empathy amongst individuals. It is clear in the existing literature that ABMs are powerful vehicles in supporting certain marginalized and vulnerable groups to make their voices heard. We argue that integrating art-based and service design methods can serve as an instrument to foster stakeholder engagement in sustainable tourism development in the municipality. Through a process-oriented lens, we describe how we employed the methodological layering of ABMs as a bottom-up approach in Utsjoki to achieve a shared understanding of sustainable tourism development in the area in a way that is acceptable to the local community.